THE RISK OF POLITICAL MANIPULATION TURNING INTO A POLITICAL INFODEMIC: PRECAUTIONS FOR GENERATION Z - Orhan, Ertuğrul Buğra (My University, 2023)
TThis article examines the notion of infodemic in relation to political manipulation, specifically focusing on Generation Z as a case study. The analysis is based on relevant literature and utilizes an inductive approach. The initial segment emphasizes the significance of mass communication and social media in the dissemination of information. Additionally, the paper delves into artificial intelligence and cybersecurity, specifically addressing the potential dangers of infodemics. Research literature indicates that Generation Z is more vulnerable to disinformation disseminated through social media platforms. Hence, it is imperative for lawmakers and members of Generation Z to actively engage in tackling this matter. Media literacy is promoted to empower Generation Z in discerning between reality and fiction. The article advocates for the development of analytical thinking skills and underscores the significance of discerning between different sources of information and trustworthy news outlets. Furthermore, there is a strong emphasis on adhering to regulations pertaining to the utilization of social media. In essence, it asserts that cooperation is required to safeguard Generation Z against political information breakouts and manipulations that may give rise to issues regarding democratic norms and societal repercussions. Additionally, greater investigation into this subject is important.
Keywords: Generation Z; Social media; Political manipulation; Infodemy